Strategi Peningkatan Produktivitas Padi Rawa Melaui Optimalisasi Pengelolaan Lahan di Sumatera Selatan - Niluh Putu Sri Ratmini; Atekan Atekan (Seminar Nasional Lahan Suboptimal, 2020)
Ratmini NPS, Atekan A. 2020. The strategi for increasing swamp rice productivity through optimizing land management in South Sumatera. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-8 Tahun 2020, Palembang 20 Oktober 2020. pp. xx. Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Swamps is one of the potential agroecosistems to be developed as agricultural land.  Swamps in South Sumatra are estimated around 3 million hectares and which is used for agriculture reached 433 thousand hectares. The main problems in swamps are land management, adoption of technology, and low socio-economic conditions, this result in slow development and low productivity. Strategy to increase land productivity by optimization land through improved irrigation and drainage sistems, balanced fertilization, amelioration, improved varieties and integrated pest control/IPC. The purpose of this paper is to review strategies for increasing swampland through land optimization.